The Existence Of Kulintang Music in Customery Marriage in Komering Family East Oku - Dedy Firmansyah; Wadiyo Wadiyo; Ayu Niza Machfauzia; Syahrul Sinaga (International Conference on Science, Education, and Technology, 2023)
This research is entitled THE EXISTENCE OF KULINTANG MUSIC IN CUSTOMERY MARRIAGE IN KOMERING FAMILY EAST OKU. Kulintang music is means of tribal society of Komering in East OKU to carry out the stage in the process of costumery marriage. That staging in customery marriage are parade process, milur dance, giving the customery law, and sada sabai dance. But in its development nowadays the existence of kulintang music is declining in customery marriage. Based on the fact, this research aims to reveal the factors that affect the existence of Kulintang Music in East OKU. The technique of collecting data to do with an observation, interviews, study says and documments. For Analysis the Existence and dinamics of the music Kulintang not just be descriptive, then this research will borrow the concepts of culture, music, and social community to have a perspective that is analytical. That study conclude that the cause of the decrease existence of the Kulintang music in East OKU is because the disappearance of clan system in 1979. Clans system that cange into district made there was no more loyality to the customery marriage process that use Kulintang music. Internal and external factor are also influence thing to the existence Kulintang music. That internal and external factor consist of management, less of capability to play Kulintang, motivation, finance, government role, and influence foreign culture.